Dinamika Sosial-Ekonomi dan Lingkungan di Wilayah Perkebunan Kelapa Sawit Merauke - Enala, Syahrabudin Husein; Jalal, Nur; Adam, Aenal Fuad (Musamus Journal of Public Administration, 2024)
Palm oil plantations in Merauke Regency play a significant role in Indonesia's economic development, but they also bring substantial social and environmental impacts. This study aims to examine the socio-economic and environmental dynamics in the area, focusing on the distribution of economic benefits, land conflicts, and ecosystem degradation. The research methodology includes field surveys, in-depth interviews with local communities and plantation workers, and analysis of secondary data from various official sources. The results show that the expansion of palm oil plantations in Merauke provides uneven economic benefits, causes land conflicts between indigenous communities and companies, and leads to significant deforestation and environmental pollution. This study highlights the need for adopting more sustainable plantation practices, protecting indigenous land rights, and diversifying the local economy to achieve more inclusive and sustainable development